Small-signal parameter extraction of asymmetric DCDMG AlGaN/GaN HEMT. Issue 1 (2nd January 2018) - Yadav, Rahis Kumar; Pathak, Pankaj; Mehra, R.M.
Abstract : Purpose: This paper aims to report small-signal parameter extraction and simulation of enhanced dual-channel dual-material gate AlGaN/GaN high electron mobility transistor (HEMT) for the first time for the characterization of a device in microwave range of frequency. Design/methodology/approach: For parameter extraction, a standard and well-known direct parameter extraction methodology is applied. Extrinsic elements of small-signal circuit model are extracted from measured S-parameters obtained using pinch-off cold field effect transistor (FET) biasing in the first step at a low frequency range and at a higher frequency range in the second step to ensure higher extraction accuracy. Intrinsic elements are extracted from intrinsic Y-parameters that are obtained after de-embedding all the extrinsic parasitic elements of the device. Figure of merits of radio frequency are also derived from the measured results and S-parameters of the proposed device. Findings: Small signal parameters of the proposed device circuit model are extracted using the standard direct parameter extraction technique. Analysis of microwave figure of merits for device include maximum oscillation frequency, cut-off frequency, current gain, transducer power gain, available power gain, maximum stable gain, transconductance, drain conductance, stern stability factor and time delay. Practical implications: The paper bridges the gaps between theory and experimental practices by validating extracted results with reported results of structurally matching devices. Originality/value: An enhanced device structure investigated for small signal parameters incorporates field plate over dual metal engineered gate to provide better electric field uniformity, effective suppression of short channel effect, reduction in current collapse, improvement in carrier transport efficiency and enhancement in drain current capabilities.